2019
DOI: 10.1002/ls.1460
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the oxidation resistance of synthetic ester oils DOA and TDTM: Experimental evaluation and theoretical calculation

Abstract: The oxidation behavior of the synthetic ester oils di‐isooctyl adipate (DOA) and tri‐isodecyl trimellitate (TDTM) was investigated by analysing the oxidation induction time and oxidation onset temperature via pressure differential scanning calorimetry tests, and the variation in viscosity after oven accelerated oxidation tests. Moreover, theoretical calculations of the fractional free volumes and oxygen diffusion coefficients of DOA and TDTM were performed, and atomistic‐scale insights into the oxidative mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The C=O is more likely to combine with these metal ions and reduce the lubricating performance. Unlike the other three esters, electrons around the C=O of trimellitate are delocalized on the phenyl group because the C=O in the molecular structure forms a conjugated system with the phenyl group [23,24].…”
Section: Electrostatic Potentialmentioning
confidence: 99%
“…The C=O is more likely to combine with these metal ions and reduce the lubricating performance. Unlike the other three esters, electrons around the C=O of trimellitate are delocalized on the phenyl group because the C=O in the molecular structure forms a conjugated system with the phenyl group [23,24].…”
Section: Electrostatic Potentialmentioning
confidence: 99%
“…Minimal changes occurred in the RCs of these compounds with heating. As summarized in Table 1, dioctyldiphenylamine (50) in the oils generated N-(2-methylheptan-2-yl)-N-phenylaniline (25) and bis(4-(tert-butyl)phenyl)amine (26), while triphenyl phosphate (28), diphenyl tolyl phosphate (29,31,32), and phenyl ditolyl phosphate (36,38,40) were produced from tri-otolyl phosphate. It was reasonably inferred that the antioxidants and antiwear agents were all unstable, even under storage conditions.…”
Section: Chemical Characterization Of Oil Samplesmentioning
confidence: 99%
“…e results indicated that the AN increased significantly and the tribological properties were improved owing to the formation of highly polar carboxylic acids and low-molecularweight monoesters. Jin et al [28] compared the decomposition of DOA to that of triisodecyl trimellitate (TDTM) using both PDSC and ReaxFF MD and proposed atomic-level oxidation mechanisms for both compounds. TDTM was found to have superior resistance to oxidation owing to dissociation of the C-O bond in the alcohol chain being initiated for TDTM, while the C-O bonds in alcohol and ester groups in DOA were susceptible to oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The high-temperature status inevitably caused rapid thermal oxidation of the synthetic ester oils to form some degradation products and/or polymerised large molecules; consequently, the harmful substances deteriorate their comprehensive performance, resulting in a short service life of the lubricants. [7][8][9] Therefore, exploring a high-efficient antioxidant agent is essential to meet the industrial requirements of synthetic ester oils.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the rapid advancement of equipment, synthetic ester oils fail to satisfy operations demand under increasingly harsh working conditions, especially the high temperature of the lubrication system 5,6 . The high‐temperature status inevitably caused rapid thermal oxidation of the synthetic ester oils to form some degradation products and/or polymerised large molecules; consequently, the harmful substances deteriorate their comprehensive performance, resulting in a short service life of the lubricants 7–9 . Therefore, exploring a high‐efficient antioxidant agent is essential to meet the industrial requirements of synthetic ester oils.…”
Section: Introductionmentioning
confidence: 99%